Peran Self Control dalam Memoderasi Pengaruh Shopping Lifestyle dan Discount terhadap Impulse Buying - Oktafianis Oktafianis; Esti Dwi Rahmawati; Khabib Alia Akhmad (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the influence of shopping lifestyle and discounts on impulse buying among Shopee users in the Solo Raya area through the moderating variable self-control. This research uses quantitative methods. The population in this study were Shopee users in Solo Raya and had made purchases at Shopee in the last 3 months. The sampling technique in this research used purposive sampling with 97 samples. Data collection is carried out online via Google Forms. Data analysis in this research used SEM (Structural Equation Modeling) via SmartPLS 4.0 software. The results of this research show that shopping lifestyle and discounts have a significant effect on impulse buying. The results of the self-control moderation analysis are able to moderate (strengthen) the influence of lifestyle shopping and discounts on impulse buying among Shopee users in the Greater Solo area.